Tamali Neogi. V.S.Naipaul: His Dark and Comic Vision (Literary Voice, 2024)
V.S.Naipaul: His Dark and Comic Vision is an insightful study by Dr. Tamali Neogi to investigate the dark and comic vision of V.S.Naipaul in his selected fiction and non-fiction. The book reveals the scholarly and perceptive venture of Neogi to unravel the creative and  proliferative  genius of Naipaul (1932-2018), a literary giant of the contemporary times “ known for his ‘terrifying honesty’ in addressing cultural dislocation and restlessness caused by migration and rapid unsettling social and technological changes” who was awarded the Nobel Prize in Literature in 2001 for mapping the predicaments of the wounded and fragmented psyches of the people of most of the post-colonial cultures and societies in various continents.